THE ABILITY OF THE 2020/2021 ACADEMIC YEARS STUDENTS OF ISLAMIC UNIVERSITY OF INDRAGIRI IN CHANGING DIRECT INTO INDIRECT SPEECH - AGUS MUSTAJIB (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The students of English study program 2019/2020 years, Islamic university of Indragiri are the students who are obliged to use English in almost all subjects. So, I am intrested to know their ability in undestanding about report speech during daring class. Reported speech is a way of expressing what other people (speakers) have said directly (direct speech). In collecting the data, a descriptive quantitative was used to find out the students’ ability in changing reported speech and this research used written test as the research instrument. The students of English study program to change report speech has score from 0 until 100 scores. The lowest score is 0 – 49 which was gotten by 5 students. And no one got the highest score. In conclusion, the students of the fourth semester, English Study Program, Islamic University of Indragiri had low ability in changing of the reported speech.